Disease‐Specific Quality of Life in Vestibular Schwannoma: A National Cross‐sectional Study Comparing Microsurgery, Radiosurgery, and Observation. (21st July 2020) - Chweya, Cynthia M.; Tombers, Nicole M.; Lohse, Christine M.; Link, Michael J.; Carlson, Matthew L.
Abstract : Objective: To examine the impact of treatment on disease‐specific health‐related quality of life (HRQOL) among patients with sporadic vestibular schwannoma (VS). Study Design: National cross‐sectional study. Setting: Tertiary referral center and the Acoustic Neuroma Association. Subjects and Methods: Adult patients with VS who completed the Penn Acoustic Neuroma Quality of Life (PANQOL) survey. Patients were classified by treatment at the most recent survey as microsurgery, radiosurgery, observation, or recently diagnosed (RD). PANQOL scores were compared among VS treatment groups and with nontumor controls using analysis of covariance. Results: A total of 1362 respondents with VS were analyzed. Total PANQOL scores differed significantly by treatment ( P =. 024) with adjusted means of 60, 63, 65, and 62 for the microsurgery, radiosurgery, observation, and RD groups, respectively. Subdomain scores for facial function, balance, hearing loss, and pain differed significantly ( P <. 05) by treatment. Comparisons that surpassed thresholds for clinical significance included microsurgery compared to radiosurgery and observation for facial function, microsurgery compared to observation and RD for hearing loss, and microsurgery compared to radiosurgery and observation for pain. Subdomain scores for anxiety, facial function, balance, hearing loss, energy, and pain and total PANQOL scores for nontumor controls were significantly higher (ie, more favorable) compared to the VS groups ( P <. 05). General health scores did not differ significantly between the nontumor controls and the VS groups ( P =. 19). Conclusion: Differences in HRQOL among treatment modalities are small and variably exceed the minimal clinically important difference. The impact of a VS diagnosis on HRQOL supersedes that of the treatment type.